Prespektif Hukum Islam Tentang Jual Beli Pakaian Bekas - Kurniawan, Danang (Sharia Faculty Islamic Economic Law Study Department, 2019)
We can get used clothing in today's era, especially big cities, but there are some people who still doubt the law of buying and selling used clothing. Learn how to buy used clothes according to the perspective of Islamic law. This is a literature study, by collecting data from various sources (Al-Qur'an, Hadith, Ijma 'and related literature books) and analyzed descriptively. Results of purchase-use-imposed-conditions; (1) harmony and conditions of sale and purchase. (2) the practice of khiyar (choosing), in this case, the purchase of the buyer gets at the time of purchase, purchase or after before the surrender is entitled to khiyar, but agrees in the transaction which both parties know and are mutually willing then do not need to represent khiyar. This research is expected to be able to provide benefits in the development of Islamic economics related to buying and selling used clothing, in the perspective of Islamic law. Practically beneficial for sellers and buyers for buying and selling activities without any doubt.